Serviço Social e Educação: uma aproximação a partir do estado da arte - Rodrigues, Rosilene Maria [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work presents the State of the Art in Theses and Dissertations of the Graduate Program in UNESP Social Work Franca, which has themes related to social work and its interface with Education Policy, presented between the years 1992-2012. This research modality have bibliographical character, it is called the State of the Art or Knowledge State. She has the object of research study academic of social impress, so also consider a social research, therefore, the theoretical basis used has dialectical perspective, given the historicity and the changes during the period and within the social reality in which the works were produced. We consider the work produced quantitatively, however from these data, we conducted a qualitative approach, in view of its significance for the people involved. The goal is to present this production characterizing it as: studied themes, levels and modality of education presented, nature of the studied institution and the period for submission of each job. Are also objectives of this dissertation: to demonstrate the conception of education contained in the works, and demonstrate professional performance by aspects presented in CFESS document: Subsídios para atuação de assistentes sociais na Política de Educação in regard to ensuring access and retention of students in educational institutions, to ensure the quality of education and ensuring democratic management of educational policy. Therefore, the first text addresses the State of the Art modality of research and methodological course made from it, at the moment we present quantitative survey data. Then we pointed out the importance of building knowledge in Social Work for sedimentation the theoretical basis which was built through graduate courses in Brazil. In that sense, also we approach aspects of the construction of knowledge in Human and Social Sciences and graduate in Brazil. Finally, we perform...

Este trabalho apresenta o Estado da Arte em Teses e Dissertações do Programa de Pós-graduação em Serviço Social da UNESP Franca, que possuem temas relacionados ao Serviço Social e sua interface com a Política de Educação, apresentadas entre os anos de 1992 a 2012. Esta modalidade de pesquisa possui caráter bibliográfico, é denominada Estado da Arte ou Estado do Conhecimento. Ela tem como objeto de estudo pesquisas acadêmicas de cunho social, por isso a consideramos também uma pesquisa social, sendo assim, a base teórica utilizada possui perspectiva dialética, tendo em vista a historicidade e as transformações ocorridas no período e dentro da realidade social em que os trabalhos foram produzidos. Consideramos os trabalhos produzidos quantitativamente, no entanto a partir desses dados, realizamos abordagem qualitativa, tendo em vista seu significado para os sujeitos envolvidos. O objetivo é apresentar essa produção caracterizando-a quanto: temáticas estudadas, níveis e modalidades de ensino apresentadas, natureza da instituição estudada e o período de apresentação de cada trabalho. São também objetivos dessa dissertação: demonstrar a concepção de educação contida nos trabalhos, e demonstrar a atuação profissional mediante aspectos apresentados no documento do CFESS: Subsídios para atuação de Assistentes Sociais na Educação, no que concerne à garantia de acesso e permanência dos alunos em instituições escolares, à garantia da qualidade do ensino e garantia da gestão democrática da política educacional. Para tanto, o texto aborda primeiramente a modalidade de pesquisa Estado da Arte e o percurso metodológico realizado a partir dela, nesse momento apresentamos dados quantitativos da pesquisa. Em seguida pontuamos a relevância da construção do conhecimento em Serviço Social para sedimentação da base teórica que foi construída mediante os cursos de pós-graduação no Brasil...
Keywords: Serviço social - Estudo e ensino; Serviço social - Pesquisa; Política social; Educação; Assistentes sociais - Educação